Da Educação Infantil para o 1º ano do Ensino Fundamental: reflexões sobre o processo de transição escolar e formação inicial de pedagogos(as) na Universidade Federal do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The changes brought about by Federal Laws n° 11.114/2005 and Law n° 11.274/2006 extended the duration of Elementary School to 9 years and made the entry of six-year-old children mandatory in the 1st year of this stage of Basic Education. In 2013, Law nº 12,796, which would establish the obligatory nature of Basic Education from 4 to 17 years old and, from this new configuration, a concern with the issue of the transition from Kindergarten to Elementary School was deepened, since now, officially, children leave the preschool and enter the second stage of Basic Education at the age of six. The legal documents establish that the transition from Kindergarten to Elementary School does not happen abruptly, as it is a potential moment of crises and ruptures, which can affect the entire learning and development process of the child. Thus, it is necessary to have pedagogical mediations that consider the specifics of childhood. Given this scenario, our research, linked to Line 3 of the Graduate Program in Education, called Education and Praxis of Educator in the face of Amazonian challenges, had as its main objective to understand which elements should be considered in the process of transition between Early Childhood Education and the 1st year of Elementary School, discussing the importance of mastering specific knowledge on the integration of the first two stages of Basic Education in the initial training of pedagogues at the Federal University of Amazonas (FUA). For this, the following specific objectives were defined: (I) to know the national public policy for the expansion of Elementary School and the entry of six-year-old children into the second stage of Basic Education; (II) discuss the pedagogical implications of a transition process that respects the specificities of children who start elementary school at the age of six; (III) analyze the syllabuses of the disciplines of the Pedagogy course at FUA, in order to understand if and how the transition process is emphasized in the disciplines that work with the specificities of Kindergarten and Early Years of Elementary School. Therefore, we rely on the Dialectical Historical Materialist method, which provides the necessary bases for the analysis of this object of investigation. As instruments of data production, bibliographic and documentary research were used. For the analysis of research data, we used the Content Analysis method. Ways for interpretation were: pre-analysis, material exploration and data processing. The results indicate the need for the initial training of pedagogues at FUA to focus more broadly on the discussion about the transition between the first two stages of Basic Education in our country, contributing more effectively to pedagogues carry out theoretical-practical work that respects the specificities of six-year-old children who enter Elementary School.
From Kindergarten to the 1st year of elementary school: Reflections on the school transition process and initial education of pedagogues at the Federal University of Amazonas
Keywords: Práticas pedagógicas; Professores - Formação; Mediações pedagógicas; Ensino e aprendizagem; Política pública de ensino; CIÊNCIAS HUMANAS; Transição escolar; Educação Infantil; Ensino Fundamental; Desenvolvimento infantil; Formação de professores